QIRA'AT AL-QUR’AN - Hakmi Hidayat; Rosssa Safira Putri Yuwono, Miftakhul Ula Irzalia Febrianti, Adisti Firnanda Pratiwi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
In general, as followers of the Prophet Muhammad SAW, it is obligatory for Muslims to know and maintain his teachings. One of the teachings inherited by the Prophet is Qira'at of the Qur'an, qira'at is a way of reading a variety of Arabic letters in the Qur'an while still paying attention to the reading rules that have been set. Therefore, to avoid deviations from the qira’at of the Qur'an, some scholars set requirements that are in accordance with the rules of good qira'at. The information elaborated regarding the qiraat of the Qur'an was obtained through data collection methods, reading and writing using books and e-journals as sources. This research is descriptive analytical, which means collecting the opinions of scholars to answer the purpose of this writing. Which results in the qira'at being greatly influenced by the background of its delivery and also its history. This led to the emergence of various types of qira’at, but the Prophet still permitted it as long as it did not violate the rules, with the aim of making it easier for Muslims to read the Al-Qur’an.